2018
DOI: 10.3390/ijerph15040577
|View full text |Cite
|
Sign up to set email alerts
|

How Long Are Cancer Patients Waiting for Oncological Therapy in Poland?

Abstract: Background: The five-year relative survival rate in Poland is approximately 10% lower compared with the average for Europe. One of the factors that may contribute to the inferior treatment results in Poland could be the long time between cancer suspicion and the beginning of treatment. The aim of the study was to determine the real waiting time for cancer diagnosis and treatment in Poland. Methods: The study was carried out in six cancer centers on a group of 1373 patients, using a questionnaire to interview p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
3
14
0
1
Order By: Relevance
“…The relationship between place of residence and delay is complex, probably influenced by healthcare-related, as well as psychosociological factors. Similarly to our data, in a Polish study of 1373 cancer patients, those from bigger cities waited significantly shorter from suspicion to diagnosis than patients living in smaller cities [ 14 ].…”
Section: Discussionsupporting
confidence: 87%
“…The relationship between place of residence and delay is complex, probably influenced by healthcare-related, as well as psychosociological factors. Similarly to our data, in a Polish study of 1373 cancer patients, those from bigger cities waited significantly shorter from suspicion to diagnosis than patients living in smaller cities [ 14 ].…”
Section: Discussionsupporting
confidence: 87%
“…The rationale for this study was to figure out if there are factors which may correlate with SDI/STI (SDI: suspicion—diagnosis interval; STI: suspicion—treatment interval) and could be responsible for prolonged waiting times for oncological treatment in Poland in general, not only for prostate cancer. We have previously published a similar study of the general Polish cancer patient population which included common cancer diagnoses [12]. We have deliberately excluded prostate cancer patients from the previous analyses due to the relatively slow progression of prostate cancer in relation to other common cancers which does not justify efforts to shorten STI.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients who declared difficulties during the diagnostic process, 4% of patients received a refusal of a referral for examination, 63% of patients waited a long time for a test/visit, 24% of patients waited a long time to receive treatment and 19% of patients declared other problems. The previously published results showed the waiting time for diagnosis and treatment after cancer suspicion in Poland is too long (about 11 weeks) [28,29]. The presented study showed that patients with a higher education are more aware of the delay in the diagnosis.…”
Section: Discussionmentioning
confidence: 63%
“…Patients who declared more difficulties during treatment were as follows: women, younger patients, those that were professionally active, those with a higher education, and those living in cities and in the southern regions of Poland. We earlier published [29] that the patients who were likely to wait significantly longer for their diagnosis from cancer suspicion were pensioners, and also that the waiting time was correlated with region. The factors that significantly influenced the shorter time from diagnosis to treatment were as follows: higher education, place of residence in larger cities, and professionally active.…”
Section: Discussionmentioning
confidence: 99%